Dietary Cholesterol and Plasma Lipoprotein Profiles: Randomized-Controlled Trials - Griffin, John D. (2013)
Early work suggested that dietary cholesterol increases plasma total cholesterol concentrations in humans. Given the relationship between elevated plasma cholesterol concentrations and cardiovascular disease risk dietary guidelines have consistently recommended limiting food sources of cholesterol. Current intakes are approaching recommended levels. Recently there have been calls to reassess the importance of continuing to recommend limiting dietary cholesterol. Over the past 10 years there have been a limited number of studies addressing this issue. Striking among these studies is the high degree of variability in background diet, subject characteristics and study design. Within the context of current levels of dietary cholesterol intake, the effect on plasma lipids concentrations, with primary interest in LDL-C cholesterol concentrations, is modest and appears to be limited to population subgroups. In these cases, restrictions in dietary cholesterol intake are likely warranted. The biological determinants of inter-individual variability remain a relatively understudied area.